2023
DOI: 10.4269/ajtmh.22-0396
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices on Cholera and Water, Sanitation, and Hygiene among Internally Displaced Persons in Cabo Delgado Province, Mozambique

Abstract: In disaster situations, cholera outbreaks represent a public health emergency due to their high fatality rates and high spreading risk through camps for refugees and internally displaced persons (IDPs). The aim of this study is to examine water, sanitation, and hygiene attitudes and cholera knowledge, attitude, and practice (KAP) among people living in resettlement sites in Cabo Delgado, the northernmost province of Mozambique. Between January 1 and March 31, 2022, a cross-sectional survey was conducted by adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moreover, cyclones Idai and Kenneth created in 2019, respectively, 478,000 and 24,000 new IDPs. In this context, where overpopulation and low hygienic-sanitary conditions coexist, cholera outbreaks, along with other vaccine-preventable diseases such as measles, were more frequently reported (30).…”
Section: Direct and Indirect Health Impactmentioning
confidence: 99%
“…Moreover, cyclones Idai and Kenneth created in 2019, respectively, 478,000 and 24,000 new IDPs. In this context, where overpopulation and low hygienic-sanitary conditions coexist, cholera outbreaks, along with other vaccine-preventable diseases such as measles, were more frequently reported (30).…”
Section: Direct and Indirect Health Impactmentioning
confidence: 99%
“…20 Barriers to hand washing in some areas included the lack of soap and water and insufficient knowledge of key moments for hand washing. 21,28,29 In camp settings, people were highly dependent on soap distribution. Data from the Maratane refugee camp highlighted that only 11 per cent of assessed households had a hand washing facility at home and that soap and/or ash was present at only half of the hand washing stations.…”
Section: Hygienementioning
confidence: 99%
“…However, cost concerns lead many to rely on herbal remedies and home treatments or to seek traditional medical care as first-line treatment. 29,33,36,38,39 This is particularly an issue for female caregivers. It is not uncommon for multiple forms of care to be sought, particularly for small children, and traditional healers, called curandeiros, are often first consulted followed by a visit to a health facility.…”
Section: Alternative Providers and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is against the backdrop of the Sustainable Development Goals (SDGs) launched in September 2015 that committed to "adequate and equitable sanitation and hygiene for all and end open defecation, paying special attention to the needs of women and girls and those in vulnerable situations" (2). Evidence has shown that lack of safely managed sanitation is among the leading cause of mortality and morbidity especially among children under five years old (3)(4)(5). Furthermore, lack of safely managed sanitation leads to economic loses as a result of productive man hours spent tending to the sick especially for women, premature death and treatment costs (6).…”
Section: Introductionmentioning
confidence: 99%